Companies and climate change : theory and law in the United Kingdom - Benjamin, Lisa (Writer of Companies and climate change) (Cambridge : Cambridge University Press, 2021)
Companies lie at the heart of the climate crisis and are both culpable for, and vulnerable to, its impacts. Rising social and investor concern about the escalating risks of climate change are changing public and investor expectations of businesses and, as a result, corporate approaches to climate change. Dominant corporate norms that put shareholders (and their wealth maximization) at the heart of company law are viewed by many as outdated and in need of reform. Companies and Climate Change analyzes these developments by assessing the regulation and pressures that impact energy companies in the UK, with lessons that apply worldwide. In this work, Lisa Benjamin shows how the Paris Agreement, climate and energy law in the EU and the UK, and transnational human rights and climate litigation, are regulatory and normative developments that illustrate how company law can and should act as a bridge to progressive corporate climate action.
Theorising the company in the context of climate change -- English company law and climate change -- International and transnational climate change law and policies -- Domestic climate and energy regulation -- Companies, human rights, and climate litigation -- Fiscal barriers and incentives to corporate climate action.
Title from publisher's bibliographic system (viewed on 09 Apr 2021).
Keywords: Climatic changes -- Law and legislation -- Great Britain; Liability for environmental damages -- Great Britain; Corporation law -- Great Britain; Social responsibility of business -- Law and legislation -- Great Britain; Corporations -- Environmental aspects -- Great Britain; Industrial management -- Environmental aspects -- Great Britain; Climatic changes -- Government policy -- Great Britain; Climatic changes -- Government policy -- European Union countries; Environmental policy -- Great Britain